Validity of the stamina index test for monitoring elite athletes - Hill, M. R.; Motl, R. W.; Estle, J.; Gaskill, S. (Medicine & Science in Sports & Exercise, 1997)
The effectiveness of the Stamina Index Test (SIT) as a monitoring tool of morning heart rates in elite level Nordic and biathlon skiers during a winter of racing was assessed. Skiers (M = 2; F = 6) performed the SIT every morning for six months. SIT involves using a heart-rate monitor to record resting (HR1), elevated after 30 knee-bends (HR2), and recovery heart rates (HR3) and is calculated as (HR1+HR2+HR3-200)/20. Variables assessed were fluid intake prior to SIT, hours of sleep, internal variables, training hours, and training intensity. Cannonical correlation analyses related the variables. Two significant correlations were revealed. 1.More sleep was associated with lower heart rates and SIT values as well as enhanced-feeling status, and 2.lower elevated heart rates and enhanced-feeling status were associated with fewer colds and internal problems. Implication: Sleep is a significant value for producing better physical function and mental states. This should be a major factor involved in recovery periods or taper periods prior to important competitions. Elevated heart rates also indicate poor status of feeling and health although the degree of association is relatively low. The provision of opportunities to obtain adequate sleep is a factor that must be considered in the training life of an elite athlete.